2020
DOI: 10.1093/ibd/izaa023
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to and Screening Visit Results of the Multicenter Pediatric Crohn’s Disease Growth Study

Abstract: Background Statural growth impairment is more common in males with Crohn’s disease (CD). We assessed sex differences in height Z score differences and bone age (BA) Z scores and characterized age of menarche in a novel contemporary cohort of pediatric CD patients undergoing screening for enrollment in the multicenter longitudinal Growth Study. Methods Crohn’s disease patients (females with chronological age [CA] 5 years and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The incidence of IBD is high and increasing, especially in early life (Benchimol et al, 2017(Benchimol et al, , 2014Ng et al, 2017). IBD is particularly challenging when it develops in children; delay in the onset and progression through puberty is common in this population, and can result in reduced adult height and sexual immaturity (Gupta et al, 2020). In this study, we assessed the microbiome, intestinal, endocrine, brain, and behavioral effects of repeated DSS-induced gut inflammation in early life.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of IBD is high and increasing, especially in early life (Benchimol et al, 2017(Benchimol et al, , 2014Ng et al, 2017). IBD is particularly challenging when it develops in children; delay in the onset and progression through puberty is common in this population, and can result in reduced adult height and sexual immaturity (Gupta et al, 2020). In this study, we assessed the microbiome, intestinal, endocrine, brain, and behavioral effects of repeated DSS-induced gut inflammation in early life.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al (6,7) observed that the median onset of menarche was delayed from 12.5 years to 13.9 years in girls with CD and suggested that delayed BA could allow for continued growth in patients with older CA. This was later supported by retrospective data from the ImproveCareNow registry where girls aged >15 years grew a median of 1.8 cm with CD and 1.5 cm with UC (27).…”
Section: Discussionmentioning
confidence: 99%
“…Growth impairment is a well-recognized multifactorial complication of pediatric-onset inflammatory bowel disease (IBD) and associated with the age of onset of IBD, severity of disease, nutritional insufficiency, disease location, and medication exposure (1–8). Confounding factors such as familial short stature, which is identified by low mid-parental height (MPH), can also play a role in final height (FHt).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Sex Differences in Statural Growth Impairment in Pediatric Crohn's Disease study (also known as the Growth Study), a poorer height growth in males was described: the data suggest that height gain is lower in males than females with skeletal maturation [40].…”
Section: Growth Failurementioning
confidence: 99%